A rare case of cholangiocarcinoma presenting with paraneoplastic syndrome. Issue 5 (29th July 2021) - Yung, Stephanie; Arendse, Michael; Weilert, Frank; Ko, Bong Suk
Abstract: Cholangiocarcinoma has a poor prognosis because of the poor early detection rate and limited treatment options. Therefore, it is important to understand the symptoms of paraneoplastic syndromes in order to detect occult malignancy early, when it is still at a highly treatable stage. Here, we report an extremely rare case of cholangiocarcinoma with paraneoplastic syndrome related to a clinical diagnosis of dermatomyositis (DM) sine dermatitis. A 74‐year‐old Caucasian man experienced 3 weeks of painless jaundice, progressive proximal muscle weakness and renal failure with rhabdomyolysis. Based on the results of laboratory tests and imaging (magnetic resonance cholangiopancreatography, endoscopic ultrasonography and endoscopic retrograde cholangiopancreatography) and histological examination, the diagnosis was cholangiocarcinoma. The diagnosis was consistent with cholangiocarcinoma with paraneoplastic syndrome provoked by DM sine dermatitis. He was successfully treated with biliary stent insertion and supportive management. Eventually, Whipple surgery was successfully performed. Paraneoplastic syndrome is very rare in patients with cholangiocarcinoma, and it is extremely uncommon in the setting of DM. This is the first case in New Zealand.